Problematika Keadilan mengenai Hak Asasi Manusia pada Masyarakat Indonesia: Analisis Metode Tafsir Maudhu’i - Fitri Andaryani; Iqrimatunnaya Iqrimatunnaya; Jauharah Khairun Nisa; Asep Abdul Muhyi (UIN Sunan Gunung Djati Bandung, 2023)
The problem of justice regarding human rights in Indonesia has always been a very hot issue to be studied. This study aims to discuss verses about human rights. This study uses a qualitative approach by applying the descriptive-analytical method in searching for interpretations and discussion, this study also uses the maudhu’i interpretation method in searching for verses that are relevant to human rights. The formal object of this research is the science of the Qur’an and interpretation, while the material objects are verses about human rights in (Q.S. al-A’raf: 24), (Q.S. asy-Syu'ara: 183), (Q.S. an-Nisa: 58), (Q.S. al-Maidah: 32). The results and research show that human rights have existed since ancient times and the verses we found are very relevant to existing problems, especially on human rights issues. This study concludes that (Q.S. al-A’raf: 24), (Q.S. asy-Syu'ara: 183), (Q.S. an-Nisa: 58), (Q.S. al-Maidah: 32) is relevant as a reference that a person must have fairness, especially in upholding human rights.